2013
DOI: 10.1366/12-06904
|View full text |Cite
|
Sign up to set email alerts
|

Human Hair in the Identification of Cocaine Abuse with Cantilever-Enhanced Photoacoustic Spectroscopy and Principal Component Analysis

Abstract: In this study, a novel approach combining different techniques, including Fourier transform infrared (FT-IR) spectroscopy, photoacoustic spectroscopy (PAS) with an interferometric cantilever microphone, and principal component analysis (PCA) along with a proper data preprocessing procedure, have been used in the investigation of hair samples for cocaine abuse. Hair fibers from cocaine-overdose patients have been measured using a simple procedure involving cantilever-enhanced photoacoustic Fourier transform inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…By virtue of their high sensitivity in response to pressure variations at a particular frequency, cantilever beams (CBs) are utilized as vibration or force sensors in various narrowband applications of pressure or motion detection [ 1 , 2 ]. In addition to well-established applications in atomic force microscopy (AFM) [ 3 , 4 ], scanning force microscopy (SFM) [ 5 ], photothermal spectroscopy (PTS) [ 6 ], and biomolecular sensors [ 7 ], CBs have also been explored for enhanced detection of weak acoustic waves [ 8 ], such as photoacoustic signals [ [9] , [10] , [11] ] in cantilever enhanced photoacoustic spectroscopy (CE-PAS) [ [12] , [13] , [14] , [15] , [16] ] which is a performant spectroscopy method [ 17 ] for trace detection of explosives, pollutants [ 18 , 19 ], illicit drug testing [ 20 ] and industrial monitoring [ 21 , 22 ]. It has been reported that CB enhanced microphones can offer a sensitivity that is 100 times higher than a good quality regular microphone [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of their high sensitivity in response to pressure variations at a particular frequency, cantilever beams (CBs) are utilized as vibration or force sensors in various narrowband applications of pressure or motion detection [ 1 , 2 ]. In addition to well-established applications in atomic force microscopy (AFM) [ 3 , 4 ], scanning force microscopy (SFM) [ 5 ], photothermal spectroscopy (PTS) [ 6 ], and biomolecular sensors [ 7 ], CBs have also been explored for enhanced detection of weak acoustic waves [ 8 ], such as photoacoustic signals [ [9] , [10] , [11] ] in cantilever enhanced photoacoustic spectroscopy (CE-PAS) [ [12] , [13] , [14] , [15] , [16] ] which is a performant spectroscopy method [ 17 ] for trace detection of explosives, pollutants [ 18 , 19 ], illicit drug testing [ 20 ] and industrial monitoring [ 21 , 22 ]. It has been reported that CB enhanced microphones can offer a sensitivity that is 100 times higher than a good quality regular microphone [ 23 ].…”
Section: Introductionmentioning
confidence: 99%